A Study of compression strength and flexural strength for Polymer Concrete - Mohamed, Mohamed R .; ALdeen, Sewench Noor; Abdulrazzaq, RawabiI (Iraqi Journal of Science, 2022)
Polymer concrete were prepared by mixing epoxy resin with sand particles in three different grain size (150-300) , (300-600 ) and (600- 1200) μm respectively. The percentage of epoxy was 15%, 20 %, 25% and 30% wt of the total weight. Compression strength and flexural strength tests were carried out for the prepared samples.The percentages of epoxy resin at 20% wt and 25% wt showed best mechanical properties for all grain sizes. These percentages were adopted to fill the voids between particles sand have two different size ranges (150-600) μm and {(150-300) & (600-1200)} μm respectively to obtain more dense material. The results showed that the strength of polymer composite at 20% resin is higher than 25% resin.